RÛH IN THE QUR’AN: AN ANALYSIS OF AL-NAISÂBÛRÎ’S EXEGESIS - Salbiyah, Siti; Wardani, Wardani; Hanafi, Hanafi (UIN ANTASARI BANJARMASIN, 2025)
The concept of rûh has been a subject of profound intellectual inquiry within the domain of Islamic thought, particularly within the discipline of Qur'anic exegesis. While the Qur'an itself acknowledges the limited knowledge granted to humanity regarding rûh (Q.S. al-Isra'/17:85), various interpretations have emerged to explore its possible meanings. This study provides a focused analysis of rûh through the lens of al-Naisâbûrî's tafsir Gharâ'ib al- Qur'ân wa Raghâ'ib al-Furqân. Employing a qualitative, descriptive-analytical approach rooted in library research, the study reveals that al-Naisâbûrî provides a multidimensional interpretation of rûh, including meanings such as the soul, divine revelation, the angel Gabriel, and the Qur'an. His exegetical approach combines the tahlîlî method with isyârî tendencies, reflecting an effort to balance the exoteric and esoteric dimensions of meaning. This research makes a significant contribution to the field of Qur'anic studies by underscoring al-Naisâbûrî's distinctive integration of rational, mystical, and linguistic approaches in interpreting rûh, thereby offering novel insights into the interpretive diversity inherent within classical Islamic scholarship.